Deep Large Binocular Camera r-band Observations of the GOODS-N Field. (1st February 2023) - Ashcraft, Teresa A.; McCabe, Tyler; Redshaw, Caleb; Windhorst, Rogier A.; Jansen, Rolf A.; Cohen, Seth H.; Carleton, Timothy; Ganzel, Kris; Koekemoer, Anton M.; Ryan, Russell E.; Nonino, Mario; Paris, Diego; et al.
Abstract: We obtained 838 Sloan r -band images (∼28 hr) of the GOODS-North field with the Large Binocular Camera (LBC) on the Large Binocular Telescope in order to study the presence of extended, low surface brightness features in galaxies and investigate the trade-off between image depth and resolution. The individual images were sorted by effective seeing, which allowed for optimal resolution and optimal depth mosaics to be created with all images with seeing FWHM < 0.″9 and FWHM < 2.″0, respectively. Examining bright galaxies and their substructure as well as accurately deblending overlapping objects requires the optimal resolution mosaic, while detecting the faintest objects possible (to a limiting magnitude of m AB ∼ 29.2 mag) requires the optimal depth mosaic. The better surface brightness sensitivity resulting from the larger LBC pixels, compared to those of extant WFC3/UVIS and ACS/WFC cameras aboard the Hubble Space Telescope allows for unambiguous detection of both diffuse flux and very faint tidal tails. Azimuthally-averaged radial surface brightness profiles were created for the 360 brightest galaxies in each of the two mosaics. On average, these profiles showed minimal difference between the optimal resolution and optimal depth surface brightness profiles. However, ≲15% of the profiles show excess flux in the galaxy outskirts down to surface brightness levels of μ r AB ≃ 31 mag arcsec −2 . This is relevant to Extragalactic Background Light (EBL) studies as diffuse light in the outer regions of galaxies are thought to be a major contribution to the EBL. While some additional diffuse light exists in the optimal depth profiles compared to the shallower, optimal resolution profiles, we find that diffuse light in galaxy outskirts is a minor contribution to the EBL overall in the r -band.